1999
DOI: 10.1159/000030074
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Ruboxyl, a Nitroxyl Derivative of Daunorubicin, on Experimental Models of Colorectal Cancer Metastases

Abstract: We evaluated the activity of ruboxyl (Rbx), a nitroxyl analogue of daunorubicin (Dauno), in experimental models of hepatic metastases from colorectal carcinoma (CRC) and compared it with its parent compound and with 5-fluorouracil (5FU). In mice treated by intraperitoneal injections Rbx and 5FU proved more effective than Dauno: the Index of Inhibition of Metastases in comparison with controls was 43% for Dauno, 70% for 5FU and 84% for Rbx. In BDIX rats implanted with the syngeneic cell line DHD K12/TRb, both R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Another orthotopic hepatic model involves laparotomy to inject SW480 human CRC cells into the cecum of the animal that results in liver tumor formation after 8 weeks (Ding et al, 2011). Furthermore, additional orthotopic liver and lung metastasis models also include surgery and injection or implantation of human tissue into immune compromised animals at various tissue sites including colon and rectum, portal vein, intraperitoneal cavity, and the tail vein (Donigan et al, 2010, Ishihara et al, 2010, Naomoto et al, 1987, Sirovich et al, 1999, Sturm et al, 2003). With the above information in mind, all the current pre-clinical models of metastatic CRC progression are costly, technically challenged, time-consuming, and do not represent an in situ model of human CRC metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Another orthotopic hepatic model involves laparotomy to inject SW480 human CRC cells into the cecum of the animal that results in liver tumor formation after 8 weeks (Ding et al, 2011). Furthermore, additional orthotopic liver and lung metastasis models also include surgery and injection or implantation of human tissue into immune compromised animals at various tissue sites including colon and rectum, portal vein, intraperitoneal cavity, and the tail vein (Donigan et al, 2010, Ishihara et al, 2010, Naomoto et al, 1987, Sirovich et al, 1999, Sturm et al, 2003). With the above information in mind, all the current pre-clinical models of metastatic CRC progression are costly, technically challenged, time-consuming, and do not represent an in situ model of human CRC metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…At present, it is not clear which role RBX may play in hematologic oncology and in the treatment of solid tumors [10, 18]; this compound also deserves a careful evaluation as an immunosuppressive agent. On the grounds of more detailed pharmacologic studies, further investigations could be planned in WD patients at poor prognosis in an earlier stage of disease, to avoid heavy pretreatment immunosuppression, and in patients with other follicular low-grade lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…In human MCF-7 cells, the stable nitroxide 4-hydroxy-2,2,6,6-tetramethylpiperidine-N-oxyl is able to induce cell damage; this may be associated with HNO reactivity (51). Intraperitoneal injections ruboxyl, a HNO analog of daunorubicin, and 5-fluorouracil reduces the development of liver metastases in experimental mouse models of colorectal cancer (138). It has been found that diazeniumdiolate-based HNO-releasing aspirin exhibits enhanced cytotoxicity toward nonsmall cell lung carcinoma cells but not endothelial cells (13), suggesting cancer-specific sensitivity.…”
Section: Role Of Hno Donors or Its Derivatives In Different Cancersmentioning
confidence: 99%